Wheat Production Across East Africa: Trend, Instability, and Decomposition Analysis Using Time Series Approach - Habtamu Mossie Andualem; Mesfin Bekele Gebbisa; Zsuzsanna Bacsi (Journal of Sustainable Agriculture and Environment)
ABSTRACT Measuring agricultural growth and variability is key to tracking output changes. East African wheat production is below its potential, with limited data and analysis over time. As a result, this study examines the growth patterns, variability, and instability of wheat production in East Africa, specifically in Ethiopia, Kenya, Uganda, Rwanda, and Tanzania, between 1993 and 2023. To analyse and estimate wheat production trends, instability with regional disparity, and decomposition across East Africa's top wheat‐producing countries, a 30‐year data series with different secondary data, mostly the FAOSTAT database, was divided into three sub‐periods: Period I (1993/94‐2002/03), Period II (2003/04‐2012/13) and Period III (2013/14‐2022/23), even though compound growth rates, a semi‐logarithmic trend model, a differential equation approach for decomposition analysis, and the Cuddy‐Della Valle Index were utilised. Wheat production and productivity in Eastern Africa exhibited a general upward trend, primarily attributed to land expansion rather than breakthroughs in yield. Ethiopia became the leading producer, whereas Uganda has shown consistent and significant growth. Conversely, Kenya and Tanzania experienced decreasing trends in productivity within cultivated areas. Instability analysis indicates that Uganda exhibited the highest stability in production at 7.32%, whereas Rwanda and Tanzania taught greater volatility, with rates of 46.74% and 32.15%, respectively. The decomposition analysis reveals that the increase in farming areas contributed to 73.1% of the recent production growth. East African countries must prioritise productivity‐enhancing wheat production by implementing modern farming technologies, employing improved varieties, increasing irrigation, and encouraging climate‐resilient practices to ensure sustainability and improve regional food security, regional trade connectivity and for further encroachment of East Africa community.